Diversification of the Egg Production Chain and Opportunities for Producers to Expand Their Businesses - Guastali , Ana Carolina da Angela; Pigatto , Gessuir; Pigatto , Giuliana Aparecida Santini; Simões , Rebeca Delatore; Andrade , Maria Aparecida Flores de Sousa Junqueira de (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The egg industry is an essential part of the Brazilian economy, as it provides an important source of protein for the population. Additionally, it is a sector responsible for generating significant employment and income for a large portion of the population. However, despite its importance, the egg industry in Brazil faces several challenges in different aspects. Considering the rapid progress in laying hen production and the growing demand for high-quality protein, the sector must continue evolving to meet new market demands and challenges. To ensure its sustainability and competitiveness, one way is through the diversification of the egg production chain, focusing on market, business, and production levels. Thus, this study aims to analyze the diversification of the egg production chain in Brazil, emphasizing its alignment with the Sustainable Development Goals (SDGs) established by the United Nations in 2015. A literature review methodology was adopted, encompassing peer-reviewed journal articles, government reports, and relevant published works. Despite the limited number of studies on the subject, an integrated analysis shows that diversification techniques have become a promising option to boost the egg market, as consumers are increasingly demanding and concerned about the quality, health impact, and environmental sustainability of products and foods.